The role of serum Dickkopf‐1 in predicting 30‐day death in severe traumatic brain injury - Ke, Xin (Brain Behav, 2020)
OBJECTIVE: Dickkopf‐1 (DKK‐1), an inhibitor of the canonical/‐catenin cascade of the Wnt pathway, was upregulated in brain tissues of hemorrhagic stroke rats, and its rising circulating levels were associated with poor prognosis of acute ischemic stroke patients. We attempted to ascertain the relationship between serum DKK‐1 levels and 30‐day death after severe traumatic brain injury (sTBI). MATERIALS AND METHODS: Serum DKK‐1 levels were gauged in a total of 94 sTBI patients and 94 healthy controls. Trauma severity was assessed using Glasgow Coma Scale (GCS) and Rotterdam classification based on head computerized tomography scan. Prognostic variable was 30‐day death. RESULTS: Compared with controls, serum DKK‐1 levels were substantially elevated in patients (median value, 3.7 versus 1.0 ng/ml). Area under receiver operating characteristic curve was 0.802 (95% confidence interval (CI), 0.708–0.877) for predicting 30‐day death. Adjusted logistic regression showed that serum DKK‐1 levels above 3.7 ng/ml remained as an independent marker of 30‐day death (odds ratio, 8.573; 95% CI, 1.386–53.020) and overall survival (hazard ratio, 7.322; 95% CI, 1.320–40.622). An intimate correlation existed between DKK‐1 levels and GCS scores (r = −.649) in addition to Rotterdam classification (r = .664). CONCLUSIONS: High serum levels of DKK‐1 are closely associated with increasing severity and rising short‐term mortality of sTBI.